2005
DOI: 10.1117/12.620037
|View full text |Cite
|
Sign up to set email alerts
|

Carbon window soft x-ray imaging using multilayer optics

Abstract: The paper deals with the recent results of the experiments on soft X-ray imaging of various carbon-containing objects: biological samples, artificial carbon fibres, graphite slices, etc. The working wavelength was chosen to be 4.5 nm due to high penetration ability of these soft X-rays in the carbon materials. The experimental set-up included: laser plasma Xray source (generated with the 2nd harmonics of Nd:YAG laser), scandium-based thin-film filter and highly reflective spherical multilayer mirror. The Co/C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…Thus, the structure of the C/Si bi-layer coating was determined to be amorphous. This finding was also in agreement with other works which reported that sputtered silicon and carbon films have amorphous structures [22][23][24]. EDS analysis of the C/Si bi-layer coating surface showed that there was no particular contamination on the surface.…”
Section: Synthesis and Characterization Of C/si Bi-layer Coatingssupporting
confidence: 93%
“…Thus, the structure of the C/Si bi-layer coating was determined to be amorphous. This finding was also in agreement with other works which reported that sputtered silicon and carbon films have amorphous structures [22][23][24]. EDS analysis of the C/Si bi-layer coating surface showed that there was no particular contamination on the surface.…”
Section: Synthesis and Characterization Of C/si Bi-layer Coatingssupporting
confidence: 93%
“…More details on the use of Co/C multilayer for the soft x-ray optics in the "carbon window" can be found in Refs. 15,16 . Since the optics is to be used in conjugation with a broadband plasma soft X-ray source, no special attention should be paid to the accurate tuning the working reflectivity bands to the wavelength of the source.…”
Section: Reflective Multilayer Coatings For the Schwarzschild Objectivementioning
confidence: 97%
“…In these cases, Co/C and Ni/C, which form the sharpest interfaces, are the materials of choice [27]. The best performance at near-normal incidence has been achieved with Co/C multilayer optics showing a reflectance of 15% [28]. It should be noted that Co and Ni are the only materials that have a positive ΔΗ f when combined with C. investigated systems.…”
Section: Carbon Edgementioning
confidence: 99%